Teachers conceptualizing and developing assessment for skill development: Trialing a maker assessment framework. Issue 4 (15th October 2021) - Lock, Jennifer; Becker, Sandra; Redmond, Petrea
Abstract: A makerspace is a place where people create artifacts while sharing ideas, equipment, and knowledge. In so doing, makers develop a range of knowledge and skills, such as creativity, problem-solving, collaboration, and self-regulation, to help them achieve their goals. These skills are broadly touted as key for learning and transferable across disciplines and making contexts. This article will first review the state of play in the literature to assess skill development. Secondly, itreports on the trial of an assessment framework developed through a literature review and implemented in a maker learning environment with an elementary school context. Finally, the article concludes with implications for practice.